Frontispiece: Effective Surface Functionalization of Carbon Fibers for Fiber/Polymer Composites with Tailor‐Made Interfaces. Issue 2 (28th October 2014) - Shiba, Kota; Tagaya, Motohiro; Samitsu, Sadaki; Motozuka, Satoshi
Abstract: Composites between carbon fibers (CFs) and heterogeneous materials have been widely studied and their fabrication techniques have been developed. However, their hydrophobic surfaces make it difficult to disperse CFs into hydrophilic resins, which results in weak junctions with ceramics. To develop high‐strength composite fibers, it is important to design interfacial chemical bonds. Thus, surface‐modification techniques of CFs have recently become the main focus and their interfaces have been characterized by various analytical methods. In this Minireview, various techniques that modify the CF surface by coating with inorganic polymers (metal oxide compounds) are highlighted, and the applications of novel nanocomposite fibers are also described. Furthermore, interfacial bonds between CFs and polymer resins are reviewed and discussed in terms of CF‐reinforced plastics and their future prospects. Abstract : The frontispiece shows a representative scheme for various functional composites based on carbon fiber (CF) prepared using polymer chemistry, inorganic synthetic chemistry, and powder technology. The Minireview by Motohiro Tagaya et al. onpage 197 ff. outlines the basic properties of CFs, their surface functionalization, and the use as polymer composites. The functionalization can be achieved through physical, chemical, or electrochemical treatment. In particular, chemical coating with inorganic oxides provides not only a variety of functionalities originating from the combination of CF and inorganic oxides but also a modified surface, which has affinity with polymers. In addition, characterization techniques for the interfaces of the composites are highlighted.